Anticholinergic burden: considerations for older adults. (23rd December 2016) - Kouladjian O'Donnell, Lisa; Gnjidic, Danijela; Nahas, Rayan; Bell, J. Simon; Hilmer, Sarah N.
Abstract: Anticholinergic medications are frequently used in older adults to manage a wide range of chronic diseases. Anticholinergic burden associated with the use of multiple medications with anticholinergic effects is cumulative within an individual, and older adults are particularly susceptible to the adverse effects of these medications. These include dry mouth resulting in poor oral health, constipation, urinary retention and confusion. Use of anticholinergic medications has been associated with impaired cognitive and physical function, increased risk of falls, vascular events and hospitalisation. Consideration of anticholinergic burden is an important component of medication management for older adults. Several measures have been developed and validated to quantify anticholinergic burden, such as the Anticholinergic Drug Scale, Anticholinergic Risk Scale and the Anticholinergic Cognitive Burden scale. However, the evidence for translation of these measures into clinical practice is limited. This narrative review provides a brief clinical overview of the pharmacology of anticholinergic medications in the context of older adults, summarises approaches to measure anticholinergic burden, reviews recent evidence of the clinical impact of anticholinergic medications and discusses deprescribing strategies to manage anticholinergic burden for older adults in clinical practice.